Paleosecular variation and time-averaged field recorded in late Pliocene-Holocene lava flows from Mexico - Mejia, V.; Böhnel, H.; Opdyke, N. D.; Ortega-Rivera, M. A.; Lee, J. K W; Aranda-Gomez, J. J. (Geochemistry, Geophysics, Geosystems, 2005)
This paper presents results from 13 paleomagnetic sites from an area west of Mexico City and 7 sites from an area of dispersed monogenetic volcanism in the state of San Luis Potosi, accompanied by seven 40 Ar/ 39 Ar radiometric dates. An analysis of secular variation and time-averaged paleomagnetic field in the Trans-Mexican Volcanic Belt (TMVB), using compiled data both newly obtained and from the literature, is presented. Interpretation can best be constrained after excluding from the data set sites that appear to be tectonically affected. The selected data include 187 sites of late Pliocene-Holocene age. The mean direction among these sites is Dec = 358.8°, Inc = 31.6°, α 95 = 2.0°, k = 29. This direction does not overlap the expected geocentric axial dipole (GAD) but is consistent with a GAD plus a 5% quadrupole. The virtual geomagnetic pole scatter of this group of sites (12.7°, with lower and upper 95% confidence limits of 11.9° and 14.1°) is consistent with the value expected from Model G (13.6°).